Folic acid supplements during early pregnancy and likelihood of multiple births: a population-based cohort study. - Li Z; Gindler J; Wang H; Berry RJ; Li S; Correa A; Zheng J; Erickson JD; Wang Y; Li, Zhu; Gindler, Jacqueline; Wang, Hong; et al. (Lancet, 2003)
Background: Folic acid supplements are recommended for women of childbearing age to prevent neural tube defects in their offspring. Results of some studies, however, suggest an increase in multiple births associated with use of vitamin supplements that contain folic acid during pregnancy. Our aim was to assess this association.Methods: We used data from a population-based cohort study from which we assessed the occurrence of multiple births in women (n=242015) who had participated in a campaign to prevent neural tube defects with folic acid supplements (400 microg per day) in China. Folic acid use was ascertained before pregnancy outcome was known. We studied the relation between multiple births and any use of folic acid pills before or during early pregnancy; additionally, we investigated mechanisms by which folic acid could potentially affect the occurrence of multiple births by examining pill-taking at three time periods: before ovulation, around the time of fertilisation, and after conception.Findings: 1496 (0.62%) multiple births occurred in a cohort of 242015 women who had registered with the study between October, 1993, and September, 1995, and who had a pregnancy not affected by a birth defect; the rate of multiple births in women who did and did not take folic acid before or during early pregnancy was 0.59% and 0.65%, respectively (rate ratio 0.91; 95% CI 0.82-1.00).Interpretation: Our findings suggest that consumption of folic acid supplements during pregnancy is not associated with an increased occurrence of multiple births.